Методичні аспекти формування системи показників аналізу ділової активності підприємства - Рубан, Ліна Олегівна; Гриценко, Лариса Василівна (НТУ "ХПІ", 2016)
У статті розглянуті сучасні методичні підходи до аналізу та оцінки рівня ділової активності підприємства, їх переваги та недоліки. Обґрунтована необхідність удосконалення існуючих методичних підходів до аналізу ділової активності. Доведена доцільність використання динамічних моделей для оцінки тенденції зміни ділової активності підприємства. Запропоновано систему показників, які, виступаючи в якості критеріїв оцінки ділової активності, дозволять комплексно оцінити її рівень та динаміку на підприємстві.

The concept of business activity is often used in research and in practice. However, there is no single universally recognized system of indicators that will comprehensively evaluate the level of business activity. In the article considers modern methodical approaches to analysis and assessment of business activity, their merits and demerits, and specific features of application. It justifies a necessity of improvement of existing methodical approaches to analysis of business activity. It proved the feasibility of using dynamic models to assess trends in business activity of the enterprise. It offers a system of indicators, which could stand as criteria of assessment of business activity and comprehensively evaluate the level and dynamics of business activity in the enterprise.
Methodical aspects of formation of the system indicators of analysis of business activity of the enterprise
Keywords: оборотність активів; коефіцієнт оборотності; середня тривалість обороту; ефективність використання ресурсів; asset turnover; coefficient of turnover; average duration of turnover